2007
DOI: 10.1002/jor.20500
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural adaptation in trapezial bone due to subluxation of the thumb

Abstract: Although the thumb saddle is one of the most common sites of degenerative osteoarthritis in the hand, little is known about the altered microstructure in osteoarthritic trapezial bones. External forces resulting from subluxation of the carpometacarpal joint of the thumb (CMC I) should provoke microstructural changes in the trapezium. The purpose of this study was to compare the regional differences of the microstructure between osteoarthritic and healthy trapezial bones. Fifteen trapezia harvested from female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 48 publications
4
20
0
Order By: Relevance
“…The expansile dish pattern, in contrast, had significant rimming osteophytes and loose bodies. Surgical inspection did not reveal metacarpal dysmorphology with the dish pattern, other than extrinsic osteophytes and joint eburnation in the cases of dysplastic dish shape, similar to other reports [79,80,86,107]. This is unlike posttraumatic arthritis of a Rolando fracture, where the metacarpal is fractured and becomes dysplastic yet typically the trapezial shape is unaltered.…”
Section: Macroscopicsupporting
confidence: 88%
See 1 more Smart Citation
“…The expansile dish pattern, in contrast, had significant rimming osteophytes and loose bodies. Surgical inspection did not reveal metacarpal dysmorphology with the dish pattern, other than extrinsic osteophytes and joint eburnation in the cases of dysplastic dish shape, similar to other reports [79,80,86,107]. This is unlike posttraumatic arthritis of a Rolando fracture, where the metacarpal is fractured and becomes dysplastic yet typically the trapezial shape is unaltered.…”
Section: Macroscopicsupporting
confidence: 88%
“…3 studied with micro-CT in normal and arthritic specimens demonstrated higher trabecular presence in the ulnar column of subchondral bone, with increased volume in the arthritic radial column [80].…”
Section: Microscopicmentioning
confidence: 90%
“…Current literature supports noteworthy trabecular remodeling primarily in the trapezium rather than the first metacarpal in CMC joint arthritis (13, 15, 17, 20, 24). Recent studies using high-resolution computed tomography (micro-CT) have correlated changes in trabecular bone morphology with osteoarthritis (20, 2527). These studies have demonstrated substantial deterioration in the 3-dimensional architecture of cancellous bone, leading to unfavorable alteration in mechanical properties.…”
Section: Introductionmentioning
confidence: 85%
“…Preferential wear of the volar surface of the trapezium, however, is the most common pattern of degeneration reported in the literature (9, 10, 13, 17, 18). Similarly, the mechanics of abnormal loading and wear of the metacarpal upon the trapezium, and the bony remodeling of this process, are postulated (19,20) but poorly understood; few in vivo studies of CMC joint kinematics exist (21,22). …”
Section: Introductionmentioning
confidence: 99%
“…Other finite element studies of the carpus have assigned a cortical thickness of 1 mm to the carpal bones including the trapezium. 9 , 16 Nufer et al 17 harvested 15 trapezia during trapeziectomy procedures and compared these with 80 cadaver hands without radiological signs of osteoarthritis or osteoporosis. High resolution micro CT demonstrated that the osteoarthritic trapezia had lost length, but had a 50% thicker subcortical bone layer compared to controls.…”
Section: Discussionmentioning
confidence: 99%